2009
DOI: 10.1080/01635580802582744
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Regulation of Cell Death and Survival by Hydrophobic Bile Acids in HCT116 Cells

Abstract: A secondary bile acid, namely, deoxycholic acid (DCA), has been known to promote colon tumors; on the other hand, it also induces apoptosis in several human colon cancer cell lines. A hydrophobic primary bile acid, namely, chenodeoxycholic acid (CDCA), exhibits a similar property of apoptosis induction; DCA and CDCA also trigger some specific intracellular signal pathways in the human colon cancer cell line HCT116. In this article, we report that hydrophobic bile acids induce different cellular responses depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…First, the concentration of bile acid to which cells are exposed is important, with lower concentrations stimulating proliferation and higher concentrations causing cell death. Second, cell membrane permeability is also a determining factor, with conjugated, hydrophilic bile acids generally having little or no proapoptotic activity and deconjugated, dehydroxylated bile acids being the most detrimental [16,17]. Multiple mechanisms underlie the effects of bile acids in promoting proliferation.…”
Section: Epithelial Proliferation and Deathmentioning
confidence: 98%
See 1 more Smart Citation
“…First, the concentration of bile acid to which cells are exposed is important, with lower concentrations stimulating proliferation and higher concentrations causing cell death. Second, cell membrane permeability is also a determining factor, with conjugated, hydrophilic bile acids generally having little or no proapoptotic activity and deconjugated, dehydroxylated bile acids being the most detrimental [16,17]. Multiple mechanisms underlie the effects of bile acids in promoting proliferation.…”
Section: Epithelial Proliferation and Deathmentioning
confidence: 98%
“…At relatively low concentrations, bile acids augment their effects on epithelial proliferation through inhibition of apoptosis [16], but at higher concentrations, they are proapoptotic. Apoptotic effects are directly related to bile acid hydrophobicity, with DCA, CDCA, and LCA being the most potent and hydrophilic bile acids having little or no effect [17].…”
Section: Epithelial Proliferation and Deathmentioning
confidence: 99%
“…Unlike hydrophobic bile acids such as DC and CDC (7,8), UDC did not exhibit remarkably acute cytotoxicity. Although cell proliferation was suppressed in a concentration-dependent manner, the number of HCT116 cells did not decrease, even at the highest concentration (600 µM), after 24 h (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…We have previously demonstrated that sublethal concentrations of hydrophobic bile acids protect HCT116 cells from the apoptosis induced by the hydrophobic bile acids themselves. Sublethal concentrations of bile acids effectively attenuated activation of caspase-9, whereas cytochrome c release from the mitochondria was not inhibited (8). Given that the association of procaspase-9 and Apaf-1 was reduced in the cytoprotective condition, we propose that sublethal concentrations of hydrophobic bile acids protect cells from apoptosis by inhibiting apoptosome formation.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation